Volatility transmission in maize futures markets of major exporters. Issue 3 (3rd July 2019) - Sayed, Ayesha; Auret, Christo
ABSTRACT: The United States, Brazil, Argentina and South Africa are the largest exporters of maize. This paper examines volatility transmission in maize futures listed on SAFEX, CBOT, MATBA (Argentina) and BMF (Brazil). Four multivariate GARCH models are employed to investigate the dynamics and cross-dynamics of volatility using daily data over the period 24 November 2008 to 27 December 2018. The results confirm the existence of significant spillover effects of volatility between futures markets of the leading exporters of maize. The results also highlight that the level and magnitude of interdependence between these markets have changed over time. The findings have important implications for risk management and regulation in agricultural futures markets.